Manajemen Pembelajaran Bahasa Arab Dalam Pendidikan Islam - Tamaji, Sampiril Taurus (Program Pascasarjana Pendidikan Islam Universitas Islam Darul Ulum Lamongan, 2021)
This article aims to explain the management of Arabic language learning. To achieve the learning objectives of Arabic that have been planned by an institution including madrasah, of course it takes a good Arabic learning management and in accordance with the meaning of management itself which includes planning, organizing, implementation / direction and supervision / evaluation so that the learning objectives can be achieved optimally. In this article the author uses descriptive research that is by presenting a complete picture in the form of verbal or numerical and presents basic information about a relationship and explore about a phenomenon and social reality. Based on the discussion that has been written then the author gives an outline. Arabic learning management is an attempt to manage the learning of Arabic language which includes planning, implementation and evaluation of learning in order to achieve the learning objectives effectively and efficiently